(untitled) (Economic and Political Thought, 2016)
The article aims to analyse Ukrainian foreign policy in the period 1991– 2013, i.e. since the country became independent and until Euromaidan in Maidan Nezalezhnosti in Kiev and its geopolitical and economic circumstances in the context of the present conflict between Russia and Ukraine as well as its relations with the European Union. The conflict not only drove Ukraine to economic ruin but also revealed its other weaknesses and destabilised its political and social system. It had been growing for a long time and created threat for the security of Ukraine and peace in Europe and the world. It put an end to the foreign policy of oscillating between Russia and the European Union, which Ukraine adopted when it became sovereign (1991). The Ukrainian crisis and conflict with Russia also revealed weaknesses and drawbacks of the European operation and the bankruptcy of its eastern policy. The main thesis is a conclusion that, despite the present conflict, because of geopolitical and geo-economic factors, Ukraine and Russia are in fact condemned to coexistence and the earlier all the parties to the conflict, especially the West, realise that, the easier it will be to finish the conflict, in fact a war, with benefits for all the involved parties. The European Union should do everything to help normalise the relations between the two countries and develop appropriate strategy towards both Russia and Ukraine. It is necessary to promise less to Ukraine and to stop threatening Russia with new sanctions, and act more efficiently. This requires cooperation of the EU with Ukraine and Russia, without which bringing a peaceful end to the Ukrainian-Russian conflict is impossible. This does not mean, however, that the EU should give in to Russia’s demands or admit Ukraine to the Union. On the other hand, Russia cannot violate international law and must again accept the European status quo and communicate with Ukraine, the European Union and the United States.